Biochemical and Histopathological Study of the Toxic Effects of Electronic and Conventional Cigarette Smoke on the Liver of Rats - Hakim bahlok jebur; Raghad Jawad Salman; Khalid Alyodawi (Scientific Trends, 2023)
The present study was conducted to investigate the biochemical and histopathological changes in rats’ liver induced by the toxic effects of exposure to electronic vapour and conventional cigarette smoke. The experimental work was performed using 25 rats; 10 rats were exposed to electronic cigarette vapour (ECV), 10 rats were subjected to conventional cigarette smoke (CCS), and 5 rats were recruited as a control group with no treatment. One hour daily of exposure to the ECV and CCS was followed for 40 days. The ECV and CCS were delivered to the animals via the use of a smoke chamber and were locally modified for this study. When the endpoint of the experiment was reached, the blood and liver specimens were collected from all animals for examining biochemical and histological changes. The findings of the work highlighted that significant (p˂0.05) reductions occurred in the serum amounts of albumin and cholesterol of the ECV and CCS groups when both were compared separately to the data of the control group. Moreover, serum amounts of lactate dehydrogenase (LDH) were increased significantly (p˂0.05) in the ECV and CCS groups when both were compared separately to the control group. Furthermore, significant (p˂0.05) decreases were seen in the serum amounts of the alkaline phosphatase (ALP) and aspartate transaminase (AST) of the CCS group with no significant (p˃0.05) alterations in the alanine aminotransferase (ALT). For the histological alterations, both ECV and CCS induced hepatic cell-related hydropic degeneration and intercellular sinusoidal dilation. In detail, the CCS caused some hepatic cell vacuoles, in which blood filled some of these vacuoles, however, no blood was observed in any of these vacuoles induced by the exposure to ECV. In addition, both ECV and CCS caused focalized infiltration of lymphocytes; though, CCS was identified with a less degree, especially in the portal vein and surrounding regions. Moreover, both ECV and CCS caused congestion in the portal vein region. The present findings highlight the dangerous effects of exposure to electronic and conventional cigarette smoke, affecting both biochemical and histological features in the studied rats.
Keywords: Biochemical effects, conventional smoking, electronic smoking, histological changes.